2008
DOI: 10.48550/arxiv.0804.1959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Afterglows of Swift-era Gamma-Ray Bursts II.: Type I GRB versus Type II GRB Optical Afterglows

D. A. Kann,
S. Klose,
B. Zhang
et al.

Abstract: Gamma-Ray Bursts (GRBs) have been separated into two classes, originally along the lines of duration and spectral properties, called "short/hard" and "long/soft". The latter have been conclusively linked to the explosive deaths of massive stars, while the former are thought to result from the merger or collapse of compact objects. In recent years indications have been accumulating that the short/hard vs. long/soft division does not map directly onto what would be expected from the two classes of progenitors, l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(65 citation statements)
references
References 206 publications
(513 reference statements)
6
58
1
Order By: Relevance
“…For most GRB afterglows, when accurate multi-band photometry is available (e.g., Covino et al 2008, Schady et al 2010, Kann et al 2010, the derived extinction curve is in fair agreement with what observed locally in the Small Magellanic Cloud (SMC, Pei 1992) although often, due to the limited wavelength resolution, this simply means that the observed extinction curve has to be chromatic (i.e. wavelength dependent) and featureless.…”
Section: The Extinction Curve Shapesupporting
confidence: 59%
“…For most GRB afterglows, when accurate multi-band photometry is available (e.g., Covino et al 2008, Schady et al 2010, Kann et al 2010, the derived extinction curve is in fair agreement with what observed locally in the Small Magellanic Cloud (SMC, Pei 1992) although often, due to the limited wavelength resolution, this simply means that the observed extinction curve has to be chromatic (i.e. wavelength dependent) and featureless.…”
Section: The Extinction Curve Shapesupporting
confidence: 59%
“…However, its morphology is different from typical long GRBs, being similar to the one of GRB050724, traditionally classified as a short GRB (Zhang et al, 2007;Piro, 2005). Its optical afterglow luminosity is intermediate between the traditional long and short ones (Kann et al, 2008). Its host galaxy has a moderate specific star formation rate (R Host ≈ 2M s y −1 (L * ) −1 , M vHost ≈ −15.5; Fynbo et al, 2006;.…”
Section: Introductionmentioning
confidence: 93%
“…The detection of short GRB afterglows starting in mid-2005 provided an opportunity to investigate the various progenitor models through a range of observational tests: the redshift distribution Gal-Yam et al 2008), the host galaxy demographics , the afterglow properties Gehrels et al 2008;Kann et al 2008;Nysewander et al 2009), and perhaps most importantly, their locations relative to the host galaxies (Fong et al 2010). As of mid-2010, X-ray and optical afterglows have been detected from 40 and 20 short GRBs, respectively, with the latter sample providing accurate sub-arcsecond positions.…”
Section: Introductionmentioning
confidence: 99%